Anomalously large lattice strain contributions from rhombohedral phases in BiFeO3-based high-temperature piezoceramics estimated by means of in-situ synchrotron x-ray diffraction. Issue 14 (November 2018) - Zuo, Ruzhong; Qi, He; Xie, Aiwen; Zheng, Donggeng
Abstract: Thermally-stable (0.75- x )BiFeO3 -0.25PbTiO3 - x Ba(Zr0.25 Ti0.75 )O3 (0.1 ≤ x ≤ 0.27) piezoelectric ceramics were reported to have excellent dielectric and electromechanical properties of d33 ∼405 pC/N, kp ∼46%, ε33 T /ε0 ∼1810, tanδ∼3.1% and Tc ∼421 °C close to tetragonal (T)-rhombohedral (R) morphotropic phase boundary. The dielectric measurement indicates that R ferroelectric phase is gradually transformed into relaxor ferroelectric across the phase boundary due to the substitution of BZT for BF. The transmission electron microscopy and convergent beam electron diffraction provide clear evidences that both the R-T phase coexistence and polar nanodomains contribute to enhanced piezoelectric properties at x = 0.19 through cooperatively facilitating polarization orientation. In combination with the macroscopic piezoelectric coefficient measurement, the quantitative analysis of synchrotron diffraction data under electric fields suggests that extremely large lattice strain contribution predominantly from R phases plus little extrinsic domain switching contribution should dominate the piezoelectric response of the x = 0.19 sample, mainly owing to both irreversible field-induced T to R phase transition and irreversible non-180° domain switching.